A Cross-Sectional Study to Evaluate the Prevalence and Severity of Gingivitis among High School Students in Erbil City-Iraq. - Dildar Abdullah Othman; Rawand Mohammed Muhi; Nadeen Nazar Nafie; Manar Nadhum Farman (Erbil Dental Journal)
Background and objective: There is an increase in the gingival inflammation without an associated increase in plaque level during puberty. This study aimed to find out the extensiveness and severity of gingivitis among high school students and its relation with the socioeconomic status in different areas of Erbil city.